2008
DOI: 10.1021/mp8000556
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsion Preparations of the Anticancer Drug Dacarbazine Significantly Increase Its Efficacy in a Xenograft Mouse Melanoma Model

Abstract: This article reports on the preparation of a water-soluble nanoemulsion of the highly lipid-soluble drug Dacarbazine (DAC). In addition, relative to suspensions of DAC, the nanoemulsion preparation demonstrated a lower zeta-potential (decreased negative charge, less anionic and more cationic) which has previously been associated with influencing drug membrane permeability. This study also reports that, relative to suspensions of DAC with a mean particle size of 5470 nm, nanoemulsions of DAC having mean particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…It is important to note, that at higher doses, both the NFP and PSD showed similar cytotoxic effects on both cell lines. These results are similar to previous work by our laboratory (25,26) with the chemotherapeutic drugs dacarbazine and tamoxifen, which also showed greater efficacy when utilized as a nanoemulsion formulation as compared to their suspension formulations in both a MCF-7 cancer cell line and a xenograft mouse model of melanoma.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is important to note, that at higher doses, both the NFP and PSD showed similar cytotoxic effects on both cell lines. These results are similar to previous work by our laboratory (25,26) with the chemotherapeutic drugs dacarbazine and tamoxifen, which also showed greater efficacy when utilized as a nanoemulsion formulation as compared to their suspension formulations in both a MCF-7 cancer cell line and a xenograft mouse model of melanoma.…”
Section: Discussionsupporting
confidence: 90%
“…Nanoemulsions are a class of stable emulsions formed by monolayers of phospholipids composed of a surfactant and oil suspended in water. The nanoemulsions are often referred to as "Approaching Thermodynamic Stability" [25,26]. Compared to typical suspension preparations which can be thousands of nanometers in size, nanoemulsion delivery systems utilized and reported from our lab, as well as those of others, with particle sizes approximately 100 nm or less have been shown to increase bioavailability and efficacy in vivo of delta and gamma tocopherol, aspirin, an antioxidant synergy formulation (ASF), and dacarbazine [22, 24, 26,].…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has successfully formulated nutrients such as delta-tocopherol [14] and gammatocopherol [15] into stable nanoemulsion water dispersions and demonstrated increased bioavailability compared to microemulsions using animal models. In addition, other labs using nano-preparations of paclitaxel [16], as well as our reported studies have shown increased bioavailability and efficacy of nanoformulations of anti-cancer drugs such as tamoxifen [17] and dacarbazine [18] and anti-inflammatory compounds such as aspirin [19] compared to micro-suspensions using cell culture and animal models.…”
Section: Introductionmentioning
confidence: 56%
“…Nanoemulsion delivery systems have previously been shown to improve bioavailability of nutrients such as delta-tocopherol, calcium and the vitamin-like coenzyme Q-10 molecule [14,27,28]. Pre-clinical studies have shown increased anti-cancer activity of drugs such as tamoxifen and dacarbazine, enhanced antiinflammatory property of aspirin, improved bioactivity of insulin when delivered as nanoemulsions [17][18][19]29]. Paclitaxel nanoformulation showed increased bioavailability, efficacy and reduced toxicity in a clinical study [30].…”
Section: Discussionmentioning
confidence: 99%
“…The nanoemulsions are often referred to as "Approaching Thermodynamic Stability" [25]. Compared to typical suspension preparations which can be thousands of nanometers in size, nanoemulsion delivery systems utilized and reported from our lab [28][29][30][31][32] as well as those of others with particle sizes approximately 100 nm or less have been shown to increase bioavailability and efficacy of a number of compounds [25,33,34]. The concept of zeta potential and how its reduction can be associated with increased efficacy of drug delivery systems has been raised by reports from our lab [30,33] and others [35][36][37].…”
Section: Articlementioning
confidence: 99%